Students’ Perceptions of Reflective Practices (RP) Implementation to Learn Critical Thinking (CT) in Class Discussions (CD) - Fatwassani, Rezza; Fitriati, Sri Wuli; Bharati, Dwi Anggani Linggar (English Education Journal, 2019)
The present study delivers the twelfth grade students’ experiences who implement reflective practice as a technique to learn critical thinking skills when joining the class discussion. However, their perceptions on the above activity have to be a fundamental issue for the success of learning. This descriptive qualitative case study took place at SMA N 2 Masbagik of East Lombok. It aimed to describe and explain students’ reflective practice implementation, their critical thinking manifestations, and their perceptions of the reflective practice implementation to learn critical thinking skills in class discussions. Taken from field notes observation and video recordings revealed three stages of reflection process considered by the students when implementing the reflective practice. It consisted of stating positive behaviour, ideas, and feelings (first stage), returning to experience, attending to feelings, and reevaluating experiences/events/phenomena (second stage), and making conclusion or commitment (third stage). They also showed three ways in expressing critical thinking as proposed by Halpern (2003). It consists of verbal reasoning, arguments, and making decision. Furthermore, the data from open-ended questionnaire and interview revealed the domination of positive perceptions. Through this study, the writer opens the idea to give suggestion that this activity should based on clear instructions and theoretical background to meet the teaching and learning goal.